Pengaruh Fisioterapi untuk Meningkatkan Kemampuan Motorik Kasar pada Anak Cerebral Palsy di Panti Asuhan Bhakti Luhur Surabaya - Fridolina Amfotis; Amelia Risky Idhartono; Muhammad N. Jauhari (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2025)
Physiotherapy is a healthcare field focused on restoring, maintaining, and improving an individual's physical function through therapeutic exercises, body manipulation, and the use of medical equipment. The primary goals of physiotherapy are to reduce pain, improve mobility, correct posture, and restore bodily functions impaired due to injuries, neurological disorders, or other medical conditions. One condition that requires physiotherapy is cerebral palsy, a motor development disorder that affects movement and coordination. This study aims to determine the effect of physiotherapy on improving gross motor skills in children with cerebral palsy. The research employs an experimental method with a one-group pretest-posttest design. The study subjects consist of five children with cerebral palsy residing at Bhakti Luhur Orphanage in Surabaya. Data collection was carried out through pre-test and post-test assessments to measure changes in gross motor skills after physiotherapy. The data analysis technique used inferential statistical t-tests, with results showing that tcount = 2.88 is greater than ttable = 2.132. Based on these results, Ho is rejected, and Ha is accepted, indicating a significant effect of physiotherapy on improving gross motor skills in children with cerebral palsy. This study emphasizes the crucial role of physiotherapy in helping children with cerebral palsy enhance their motor skills, positively impacting their quality of life and independence in daily activities. Therefore, physiotherapy should be part of a routine intervention for children with cerebral palsy to support optimal motor development.